Digitally Mapping Student Potential: SIMPOSIDU (Sistem Informasi Potensi Individu) For Guidance And Counseling Teachers - Abdul Hadi; Ruly Ningsih (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Teachers of guidance and counseling play a significant role in the process ofevaluating students' potential. Basically, assessing students' potential plays asignificant part in assisting them in achieving their full potential in four areas:personal, social, academic, and professional. In actuality, there are still a numberof issues with assessing students' potential, one of which is the teacher's stilllimited capacity to record and map student potential data. At the Klaten DistrictVocational High School, 40 Guidance and Counseling teachers received trainingon the Individual Potential information system (SIMPOSIDU), which enabled theteachers to systematically and comprehensively record student potential data. Theinformation is personal, social, educational, and other. The service makes itsimpler for teachers to map data about future pupils so they can assist kids inproblem-solving in accordance with their potential.